2024
DOI: 10.3233/jrs-220028
|View full text |Cite
|
Sign up to set email alerts
|

Research of Russian physicians’ opinions on tuberculosis pharmacogenetics

Abstract: BACKGROUND: There is currently no widespread implementation of pharmacogenetic testing (PGx) methods in the practice of phthisiology service. OBJECTIVE: The aim of this study is to determine how informed and prepared phthisiologists, residents, and postgraduate students of the Russian Medical Academy of Continuing Professional Education (RMACPE, Moscow) use PGx techniques in their work to improve treatment safety, predict the occurrence of adverse reactions (ADRs), and personalize therapy. METHODS: A survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although with exceptions [ 84 , 85 ], studies have shown that subjects carrying the CYP2E1 c1/c1 genotype are 2.5 times more likely to develop hepatotoxicity when compared to those with other genotypes [ 86 , 87 ]. The risk of liver damage increased 7-fold when this genetic variant was associated with NAT2 mutations, as the number of toxic metabolites was significantly increased [ 88 ]. An increased risk of liver damage was also reported in children with the CYP2E1*6 allele and *1A-*6-*1D haplotype [ 89 ].…”
Section: Antibiotics For Which the Role Of Genetics In Conditioning D...mentioning
confidence: 99%
“…Although with exceptions [ 84 , 85 ], studies have shown that subjects carrying the CYP2E1 c1/c1 genotype are 2.5 times more likely to develop hepatotoxicity when compared to those with other genotypes [ 86 , 87 ]. The risk of liver damage increased 7-fold when this genetic variant was associated with NAT2 mutations, as the number of toxic metabolites was significantly increased [ 88 ]. An increased risk of liver damage was also reported in children with the CYP2E1*6 allele and *1A-*6-*1D haplotype [ 89 ].…”
Section: Antibiotics For Which the Role Of Genetics In Conditioning D...mentioning
confidence: 99%